2023
DOI: 10.3390/agriculture13030705
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Prospects of Head Rice Yield

Abstract: Global warming poses a serious threat to food security because of its impacts on thermosensitive food crop production. Rice is of paramount significance due to the world’s three-billion-population dependence on it as a staple food. It is well established that the high temperatures at day or night times during the grain-filling period can reduce rice grain yield, although the intriguing impact of high temperatures on head rice yields (HRY) is poorly discussed. This is because high and stable HRY is vital to mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 188 publications
2
7
0
Order By: Relevance
“…In addition, HRR (%) and PGC (%) had a very weak positive correlation with a Pearson correlation coefficient (PCC) of 0.03, which was also consistent with current correlation studies and BLUP estimates ( Sanchez et al., 2023 ; Nirmaladevi et al., 2015 ; Vemireddy et al., 2015 ; Cruz et al., 2021 ; Ali et al., 2023 ). Broad-sense heritability (H 2 ) estimates were high for HRR (%) (0.99) and PGC (%) (0.98) which was consistent with similar studies ( Sanchez et al., 2023 ; Ali et al., 2023 ). The considerably low H 2 for grain aroma (0.28) suggested that its environmental influence was attributed to the experimental conditions, as pointed out in an earlier study ( Vemireddy et al., 2015 ).…”
Section: Resultssupporting
confidence: 85%
“…In addition, HRR (%) and PGC (%) had a very weak positive correlation with a Pearson correlation coefficient (PCC) of 0.03, which was also consistent with current correlation studies and BLUP estimates ( Sanchez et al., 2023 ; Nirmaladevi et al., 2015 ; Vemireddy et al., 2015 ; Cruz et al., 2021 ; Ali et al., 2023 ). Broad-sense heritability (H 2 ) estimates were high for HRR (%) (0.99) and PGC (%) (0.98) which was consistent with similar studies ( Sanchez et al., 2023 ; Ali et al., 2023 ). The considerably low H 2 for grain aroma (0.28) suggested that its environmental influence was attributed to the experimental conditions, as pointed out in an earlier study ( Vemireddy et al., 2015 ).…”
Section: Resultssupporting
confidence: 85%
“…The kinship matrix or G-matrix was developed using the 1,512 DArTseq SNP markers mapped using the 282 RILs using the GCTA software (Yang et al, 2011) with its default parameters. 3 Numbers of all DArTseq™ markers residing in each linkage group 4 Total length of chromosome measured in centimorgan (cM) of each linkage group 5 Markers coverage on each chromosome in mega-base pairs (Mb).…”
Section: Snp Marker Ltering Qtl Mapping and G-matrix Constructionmentioning
confidence: 99%
“…Reduction in HRY following heat stress events is generally attributed to increased ssuring or grain cracking, which may be caused by grain chalkiness contributing to structural weakness (Cooper et al, 2006), but contradictory ndings were found (Ali et al, 2023). Also, it was recently found that grain breakage during the de-husking or polishing milling operations was also genotype-dependent (Ali et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations